The Implementation of the Proposed Teaching Methods in the Curricula of Language Courses during the Use of Online Teaching in the Period of Covid-19: Opinions and Attitudes of Greek Teachers - Filippos Evangelou; Ioannis Fykaris (Journal of Studies in Education, 2024)
Because of the coronavirus pandemic and its consequences, distance education and, in particular, "Online Education" (OE) was used in the educational systems of many countries, as in Greece. The main objective of this application was to keep students in touch with the educational reality, but also with the teaching and learning process. On this basis, the purpose of this study is to investigate the attitudes and opinions of Greek Primary Education teachers and Secondary Education teachers' philologists regarding the implementation of the proposed methods of teaching language courses in the use of OE. Seven hundred and thirty-four teachers constituted the sample of the study. A structured questionnaire was used to carry out the research and collect the data and the main findings of the research can be summarized as follows: the teachers' attitudes and opinions regarding the correlation of the proposed teaching methods in the Curriculum - such as the possibility for all students to produce various types of spoken and written language and the units designed for the cultivation of literacy to have the form of an action plan (project), etc. - with the use of OE are approximately neutral, namely neither positive nor negative.